Can Complementary Prime-Boost Immunization Strategies Be an Alternative and Promising Vaccine Approach Against Dengue Virus? - Valdés, Iris; Lazo, Laura; Hermida, Lisset; Guillén, Gerardo; Gil, Lázaro (Frontiers in Immunology, 2019)
Dengue is one of the most important diseases transmitted by mosquitoes. Dengvaxia®, a vaccine registered in several countries, cannot be administered in non-immune individuals and children younger than nine years old, due to safety reasons. There are two vaccine candidates coursing efficacy trials, but their registration date is completely unknown at this moment. So, the development of new vaccines or vaccine strategies continues being a priority for the WHO. This work reviews some heterologous prime-boost immunization studies against important human pathogens. Besides, it reviews the results obtained using this regimen of immunization against dengue virus as a promising alternative for finding a safe and efficient vaccine. Finally, the main elements associated with this strategy are also discussed. The generation of new strategies of vaccination against dengue virus, must be directed to reduce the risk of increasing viral load through sub-neutralizing antibodies and it must be also directed to induce a polyfunctional T cell response. Prime-boost immunization strategy could emerge as an interesting approach to induce solid immunity or at least to reduce viral load after natural infection, avoiding the severe dengue. Subunit vaccine could be safe and attractive antigens for this strategy, especially proteins including B and T cells epitopes for inducing humoral and cellular immune responses, which can play an important role for controlling the disease.